2011
DOI: 10.1073/pnas.1017022108
|View full text |Cite
|
Sign up to set email alerts
|

Potential social interactions are important to social attention

Abstract: Social attention, or how spatial attention is allocated to biologically relevant stimuli, has typically been studied using simplistic paradigms that do not provide any opportunity for social interaction. To study social attention in a complex setting that affords social interaction, we measured participants' looking behavior as they were sitting in a waiting room, either in the presence of a confederate posing as another research participant, or in the presence of a videotape of the same confederate. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
345
7
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(388 citation statements)
references
References 33 publications
34
345
7
2
Order By: Relevance
“…Klin et al 2002;Nakano et al, 2010;Riby & Hancock, 2008), but is in-line with recent findings that observed no overall reduction in eye-region viewing in older, high functioning individuals with autism when only one face or person was present in the each visual stimulus (Fletcher-Watson et al 2009;Freeth et al 2010). Findings from this new cohort of participants replicated previous findings, from Freeth et al (2013a) and Laidlaw et al (2011), using equipment enabling a much more finegrained temporal and spatial analysis of eye-movements compared to these previous studies and indicate that individuals with more autistic traits are focussing on socially relevant areas within their visual field as much as individuals who show fewer autistic traits, providing the opportunity to effectively spot and process any subtle social cues that may be produced by the social partner. In contrast to the current findings, when participants viewed a video presentation of the experimenter asking questions and listening to answers in the study by Freeth et al (2013a), a simple relationship was found between reduced looking to the experimenter and more autistic traits.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Klin et al 2002;Nakano et al, 2010;Riby & Hancock, 2008), but is in-line with recent findings that observed no overall reduction in eye-region viewing in older, high functioning individuals with autism when only one face or person was present in the each visual stimulus (Fletcher-Watson et al 2009;Freeth et al 2010). Findings from this new cohort of participants replicated previous findings, from Freeth et al (2013a) and Laidlaw et al (2011), using equipment enabling a much more finegrained temporal and spatial analysis of eye-movements compared to these previous studies and indicate that individuals with more autistic traits are focussing on socially relevant areas within their visual field as much as individuals who show fewer autistic traits, providing the opportunity to effectively spot and process any subtle social cues that may be produced by the social partner. In contrast to the current findings, when participants viewed a video presentation of the experimenter asking questions and listening to answers in the study by Freeth et al (2013a), a simple relationship was found between reduced looking to the experimenter and more autistic traits.…”
Section: Discussionsupporting
confidence: 90%
“…This absence of a relationship between autistic traits and amount of time spent looking directly at the experimenter was also observed in a face-to-face interaction by Freeth et al (2013a) and when there was potential for a social interaction by Laidlaw et al (2011). The nature of this finding is different to the reduced attention to faces often observed in children with autism (e.g.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Behavioral evidence, however, from both adults (e.g. Okita et al, 2007;Laidlaw et al, 2011) and children (Kuhl et al, 2003;Goldstein and Schwade, 2008;Kirschner and Tomasello, 2009) suggests that live, interactive context significantly alters response to otherwise matched social stimuli. Adult neuroimaging research has begun to identify the neural bases of social interaction (e.g.…”
Section: Introductionmentioning
confidence: 99%